Arteriovenous fistula and pre-surgery mapping: Potential role of physical exercise on endothelial function. Issue 6 (November 2019) - Distefano, Giulio; Zanoli, Luca; Basile, Antonio; Fatuzzo, Pasquale; Granata, Antonio
Background: The success of the construction of an arteriovenous fistula for haemodialysis is related to the vascular function of the vessels involved in the anastomosis, with particular reference to radial artery distensibility after reactive hyperaemia test and to the fall of resistance index. Only few studies have evaluated the impact of exercise protocols on the endothelial and morphological characteristics of the vessels of the upper limb with inconclusive results. In this pilot longitudinal study, we aimed to evaluate the impact of a standardized exercise protocol on the haemodynamic and resistive index of the arteries of the upper limb of uraemic patients. Methods: A total of 17 uraemic patients planned to construct arteriovenous fistula at the distal third of the forearm were enrolled and followed up for 30 days. All patients performed repeated handgrips for 30 min/day. The arterial parameters were detected before and after an ischaemic stress of 5 min and radial and brachial artery flow-mediated dilation was evaluated as well as radial artery resistance index. Results: Pre-exercise measurements of radial artery diameter and resistance index and brachial artery diameter were not modified by 30 days hand physical exercise, whereas the post-exercise haemodynamic were improved. Consequently, flow-mediated dilation of the radial artery was improved (21% ± 14% vs 30% ± 19%; p = 0.03) and resistance index of the radial artery was reduced ( p = 0.02). Conclusion: Exercise has beneficial effects on endothelial function of the radial artery by resistive index and, potentially, on the outcome of the arteriovenous fistula. Further studies with larger sample size are needed to confirm our preliminary data.